Impact of vaginal brachytherapy on survival in stage I endometrioid endometrial carcinoma. Issue 6 (June 2020) - AlHilli, Mariam; Amarnath, Sudha; Elson, Paul; Rybicki, Lisa; Dowdy, Sean
ABSTRACT : Objective : To evaluate trends in use of radiation therapy and its impact on overall survival in low‐ and high‐grade stage I endometrioid endometrial carcinoma. Methods : Patients with stage I endometrial cancer who underwent hysterectomy from 2004 to 2013 were identified through the National Cancer Database and classified as: stage IA G1/2, stage IA G3, stage IB G1/2, and stage IB G3. Trends in use of vaginal brachytherapy and external beam radiation therapy were assessed. Overall survival was measured from surgery and estimated using the Kaplan‐Meier method. The effect of radiation therapy on overall survival was assessed within each stage/grade group using Cox proportional hazards analysis in propensity‐matched treatment groups. Results : A total of 132 393 patients met inclusion criteria, and 81% of patients had stage IA and 19% had stage IB endometrial cancer. Adjuvant therapy was administered in 18% of patients: 52% received vaginal brachytherapy, 30% external beam radiation therapy, and 18% chemotherapy ±radiation therapy. External beam radiation therapy use decreased from 9% in 2004 to 4% in 2012, while vaginal brachytherapy use increased from 8% to 14%. Stage IA G1/2 patients did not benefit from either external beam radiation therapy or vaginal brachytherapy, while administration of vaginal brachytherapy improved overall survival in stage IB G1/2 compared with no treatment (p<0.0001). In stage IB G1/2 and stage IA G3, vaginal brachytherapy was superior to external beam radiation therapy (p=0.0004 and p=0.004, respectively). Stage IB G3 patients had improved overall survival with either vaginal brachytherapy or external beam radiation therapy versus no treatment but no difference in overall survival was seen between vaginal brachytherapy and external beam radiation therapy (p=0.94). Conclusions : The delivery of adjuvant radiation therapy in patients with stage IA G1/2 endometrial carcinoma is not associated with improvement in overall survival. Patients with stage IB G1/2 and G3 as well as stage IA G3 are shown to benefit from improved overall survival when adjuvant radiation therapy is administered. These findings demonstrate potential opportunities to reduce both overtreatment and undertreatment in stage I endometrial cancer patients.